Learning Management In The Development Of Social Skills For Madrasah Aliyah Students (qualitative analytical descriptive study on man 1 and man 2 tasikmalaya regency) - Samrotussa’adah; Achmad Sanusi; Cahya Syaodih; Asep Ahmad Sukandar (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The background of this research is the weakness of teacher learning management in fostering students' social skills which implies the low ability of students to build oral and written communication. The focus of the problem is how to improve teacher learning management so that the development of students' social skills is increased, especially in building student's oral and written communication optimally. The purpose of the study was to find out the management of teacher learning at MAN Tasikmalaya Regency in the form of policies for planning, organizing, implementing, monitoring, learning problems and solutions in fostering students' social skills. The approach used in this research is qualitative with descriptive method. Data obtained from interviews, observations and document studies. Data analysis uses individual case data analysis techniques and cross-case data analysis (cruss-cases analysis). Checking the validity of the data is carried out through member checks, and discussions with colleagues based on the findings obtained, Learning Management at MAN 1 Tasikmalaya Regency partially has similarities with both holding scientific learning and authentic assessment referring to the 2013 curriculum and Education System Law number 20 of 2003. Learning planning in fostering students' social skills is carried out at the beginning of each school year through madrasa work meetings with the agenda of compiling and establishing operational curricula, syllabus development, preparation of annual programs (Prota), semester programs (Prosem) , learning implementation plans (RPP), preparation of teaching materials by each subject teacher, and subject cluster teams, preparation of supervision or learning evaluation tools. Organizing learning in fostering students' social skills is carried out through mapping the duties of subject teachers and extracurricular coaches, scheduling, fulfilling workloads and additional teacher assignments. The implementation of learning in social skills development is carried out through scientific learning management where students as learning subjects can observe, ask questions, collect information, associate, communicate learning materials. Supervision of learning through authentic assessments during the learning process takes place to measure students' abilities in building question-and-answer communication, reasoning, making stories orally and in writing. The development of students' social skills is carried out through oral and written communication in the management of scientific learning and authentic assessment of intracurricular and extracurricular activities can run well, although there are still shortcomings and weaknesses. Problems that arise in learning management in fostering students' social skills are accommodated through follow-up plans (RTL) and solutions for preparation for improvement of learning activities in fostering students' social skills to achieve further goals on an ongoing basis.